PERANCANGAN SIMULASI PRA UNBK BERDASARKAN JARINGAN KLIEN SERVER - Sapri Sapri; Liza Yulianti (Universitas Asahan, 2020)
Abstract- North Bengkulu 3 Vocational High School has implemented a pre-UNBK examination system using computerization which was carried out 3 times. Pre-UNBK Simulation Based on Client-Server Network was built to help students take part in the implementation of the test and introduce the examination system that already uses computerization. This simulation system is made with 2 application interface access rights namely administrators and students. Administrators can manage the data of questions, answers, and participants of the Pre UNBK simulation. While students can take the exam on the application by working on the questions that have been given. Pre UNBK simulation where this application will be stored on the server, so the client will access the application via the IP Address of the server. Based on the functions and features of the application, it has been running according to the design, and students can access the Pre UNBK simulation application simultaneously.Keywords: Simulation, Pre UNBK, Client ServerAbstrak - Sekolah Menengah Kejuruan Negeri 3 Bengkulu Utara sudah menerapkan sistem ujian pra UNBK menggunakan komputerisasi yang dilaksanakan 3 kali. Simulasi Pra UNBK Berbasis Jaringan Client Server dibangun untuk membantu siswa-siswa dalam mengikuti pelaksanaan ujian dan mengenalkan sistem ujian yang sudah menggunakan komputerisasi. Sistem simulasi ini dibuat dengan 2 hak akses antar muka aplikasi yaitu administrator dan siswa. Administrator dapat mengelola data soal, jawaban, serta peserta simulasi Pra UNBK. Sedangkan siswa dapat mengikuti ujian pada aplikasi dengan mengerjakan soal-soal yang telah diberikan. Simulasi Pra UNBK dimana aplikasi ini akan disimpan di server, sehingga client akan mengakses aplikasi lewat IP Address dari server tersebut. Berdasarkan fungsi dan fitur dari aplikasi sudah berjalan sesuai dengan rancangan dan siswa dapat mengakses aplikasi simulasi Pra UNBK secara serentak.Kata Kunci : Simulasi, Pra UNBK, Client Server